CHANGES IN DNA METHYLATION PROFILE IN TAMOXIFEN-RESISTANT MCF-7 SUBLINES - О. Е. Andreeva; V. О. Sigin; V. V. Strelnikov; A. S. Tanas; A. M. Scherbakov; M. A. Krasilnikov (Сибирский онкологический журнал, 2019)
Abstract Introduction. We have previously shown the feasibility of hormonal resistance horizontal distribution from cell to cell, with the joint cultivation of sensitive and resistant cells and/or through exosomes secreted by resistant cells. What is the mechanism of such resistance distribution, and how do cells with secondary resistance reproduce the characteristics of donor resistant cells? To answer these questions, we analyzed the overall level of DNA methylation in MCF-7 estrogen-dependent breast cancer cells and estrogen-independent sublinia.The purpose of the study was to analyze DNA methylation profiles for the development of hormonal resistance by breast cancer cells and for resistant phenotype further accession.Methods. DNA methylation was evaluated by the RRBS (Reduced Representation Bisulfite Sequencing) method in MCF-7 breast cancer cells and their resistant sublines.Results. 19 CpG dinucleotides, differentially and generally unidirectionally methylated in cells with primary and secondary resistance to tamoxifen, were detected. Differential changes in methylation were found for DNA regions that regulated the expression of six protein-coding genes: PRKCZ, TRAPPC9, AS IC2, C2CD4A, ZNF787, CRTAC 1. Bioinformatics analysis showed that two of these six genes, PRKCZ (protein kinase C Zeta) and TRAPPC9 (Trafficking Protein Particle Complex Subunit 9) were directly involved in the regulation of NF-κB activity.Conclusion. The data obtained indicate the existence of common DNA patterns, the methylation of which varies in the same direction in cells with primary and secondary resistance. The involvement of two of the identified genes in the regulation of NF-κB may indicate the inclusion of the latter in the formation of a resistant phenotype of tumor cells, even under conditions of horizontal transfer of resistance.